Utilizing electronic health records to predict acute kidney injury risk and outcomes: workgroup statements from the 15th ADQI Consensus Conference. Issue 1 (December 2016) - Sutherland, Scott; Chawla, Lakhmir; Kane-Gill, Sandra; Hsu, Raymond; Kramer, Andrew; Goldstein, Stuart; Kellum, John; Ronco, Claudio; Bagshaw, Sean
Abstract The data contained within the electronic health record (EHR) is "big" from the standpoint of volume, velocity, and variety. These circumstances and the pervasive trend towards EHR adoption have sparked interest in applying big data predictive analytic techniques to EHR data. Acute kidney injury (AKI) is a condition well suited to prediction and risk forecasting; not only does the consensus definition for AKI allow temporal anchoring of events, but no treatments exist once AKI develops, underscoring the importance of early identification and prevention. The Acute Dialysis Quality Initiative (ADQI) convened a group of key opinion leaders and stakeholders to consider how best to approach AKI research and care in the "Big Data" era. This manuscript addresses the core elements of AKI risk prediction and outlines potential pathways and processes. We describe AKI prediction targets, feature selection, model development, and data display. Abrégé Les données figurant dans les dossiers médicaux électroniques (DMÉ) sont considérables, tant au point de vue du volume que du débit ou de la variété. Ces trois caractéristiques et la tendance générale à adopter les DMÉ ont soulevé un intérêt pour appliquer les techniques d'analyse prédictive des mégadonnées aux données contenues dans les dossiers médicaux électroniques. L'insuffisance rénale aiguë (IRA) est une maladie qui convient parfaitement à une méthode de prévision et de prévention des risques: non seulement la définition acceptée de cette affection permet-elle un ancrage temporel des événements ; mais il n'existe aucun traitement une fois que la maladie est déclarée, ce qui montre l'importance d'une détection précoce. L'Acute Dialysis Quality Initiative (ADQI) a convoqué un groupe de travail constitué de leaders d'opinion et autres intervenants du milieu pour se pencher sur la meilleure façon d'approcher la recherche et les soins offerts aux patients atteints d'IRA en cette ère de mégadonnées. Le présent article traite des éléments centraux de la prévention des risques et en expose les procédures potentielles. Nous y décrivons les cibles de prévention de l'IRA, la sélection des paramètres, l'élaboration des modèles et l'affichage des données.